"What does a woman want?" The moderating effect of age in female consumption. (September 2015) - Tsarenko, Yelena; Strizhakova, Yuliya
Abstract: This study aims to improve understanding of the factors that influence female purchase behaviour in the context of intimate apparel. This study examines mediating effects of hedonic consumption and interaction with store personnel on the relationship between (a) product attributes and the fitting process and (b) actual purchases. The chronological age of consumers included as a moderator of these indirect relationships. Our findings show that mediation effect of hedonic consumption is more pronounced in younger segment while interaction with store personnel is more apparent among older segment of consumers. These findings inform retailers how to successfully serve various age groups of female consumers. Highlights: Mediating effect of hedonic consumption is stronger among younger female consumers. Mediation effect of interaction with store personnel is stronger among older female consumer. Chronological age moderates decision making process among female consumers.